Providing Ubiquitous Positioning Using Context Aware Handover Algorithm - Khan, Mohammod Sazid Zaman (2012)
This research alms to solve the problem of ubiquitous positioning by designing a context aware handover algorithm for positioning systems. The algorithm performs handover among positioning systems based on important contextual factors related to position determination with efficient use of battery. In addition, the design ensures that no positioning system is allowed to operate for an indefinite period of time without getting a position. The proposed solutions are implemented in an Android application named Locate@nav6.